Performance and Mechanism of Gas‐Solid Adsorption in a Rotating Adsorption Bed. Issue 5 (23rd March 2022) - Guo, Qiang; Zhao, Yue; Qi, Guisheng; Liu, Youzhi
Abstract: A rotating adsorption bed for adsorbing toluene by activated carbon was constructed. It was found that the adsorption capacity of the rotating bed was stronger than that of the fixed bed and showed a faster adsorption rate. The particle diffusion model showed that the adsorption process in a rotating adsorption bed was a combination of surface diffusion and particle diffusion. In the rotating adsorption bed, the contribution rate of intraparticle diffusion to the whole adsorption was the largest, and the adsorption rate of each stage of the rotary adsorption bed was higher than that of the fixed bed. The good external diffusion force of the rotating adsorption bed effectively realized the deep‐pore adsorption of the adsorbent and improved the utilization rate of the adsorbent. Abstract : The adsorption diffusion model and adsorption rate of an adsorption bed are studied, and the mechanism of gas‐solid adsorption in a rotating adsorption bed is explored in‐depth, which provides theoretical support for the further application of this technology. For this aim, a rotating adsorption bed system with activated carbon to adsorb toluene was constructed to explore the adsorption mechanism.